2014
DOI: 10.1039/c4ra08984g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of silica particles into decellularized tissue biomaterial and its effect on macrophage activation

Abstract: Secretion of signaling molecules by macrophages is induced by silica particles deposited onto decellularized tissue derived biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…On the other hand, an interesting fact is that, although metabolic activity of primary rabbit epithelial cells cultured on plain material was lower compared to control, when materials were coated with pericardial ECM hydrogel, the metabolic activity increased. Although further studies are needed to clarify the effects of ECM gel and EETs on both cell type when are used as a coating on decellularized bioscaffolds, both modified ECM gels and decellularized bioscaffolds promote anchor‐dependent cell survival 19,22,40 . In this study an EETs concentration was found that prevents a cytotoxic effect on macrophages and epithelial cells.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, an interesting fact is that, although metabolic activity of primary rabbit epithelial cells cultured on plain material was lower compared to control, when materials were coated with pericardial ECM hydrogel, the metabolic activity increased. Although further studies are needed to clarify the effects of ECM gel and EETs on both cell type when are used as a coating on decellularized bioscaffolds, both modified ECM gels and decellularized bioscaffolds promote anchor‐dependent cell survival 19,22,40 . In this study an EETs concentration was found that prevents a cytotoxic effect on macrophages and epithelial cells.…”
Section: Discussionmentioning
confidence: 74%
“…Although further studies are needed to clarify the effects of ECM gel and EETs on both cell type when are used as a coating on decellularized bioscaffolds, both modified ECM gels and decellularized bioscaffolds promote anchor-dependent cell survival. 19,22,40 In this study an EETs concentration was found that prevents a cytotoxic effect on macrophages and epithelial cells. The epithelial cell coating on the surface of bioscaffolds seems to be supported by the EETs-ECM gel modification.…”
Section: Esophageal Submucosa Bioscaffold Modified With Ecm Gel Conta...mentioning
confidence: 72%
“…Also, the incorporation of SiP in the ECM 3D network sustains the viability and function of macrophages. [27][28][29] To take advantages of this new methodology regarding the tailored properties of biocomposite hydrogels, this paper describes a novel approach where Dex is simultaneously loaded during the formation of these biocomposite hydrogels and then released at physiological conditions. The content of the SiP (0, 5 and 15 wt%) in the PPU-ECM hydrogels is explored as a variable that decisively inuences the polymerization rate, 3D network characteristics, swelling and biodegradation of the biocomposites, enhancing the controlled release of Dex and its effect on the in vitro macrophage response.…”
Section: Introductionmentioning
confidence: 99%